Do we need cross border education? A Case of Pilot Course Multi-professional Approaches to Substance Abuse Care and Working with Addicts (Journal of Comparative Social Work, 2017)
The aim of this article is to examine studentsʼ experiences of cross-border education based on a single course carried out in collaboration between two networks, Barents Cross-Border University (BCBU) and the Thematic Network of Social Work (TNSWUA), as well as the experiences of teachers in the course. The course was a part of the curriculum for the Master’s Degree Programme (BCBU) in Comparative Social Work. Most of the students were studying in this Master’s Programme, some of them were exchange students at the University of Lapland (UL) and the rest were social work students at UL and the University of Iceland (UI).  The course ran for two weeks in April 2015, and included lectures, discussions and workshops; parts of the course were delivered electronically, while other sections were delivered by teachers on-site.This course provided a broad multi-professional introduction to the field of addiction and substance abuse care. Students learned about screening the alcohol culture and the relationship between society, addiction, gender, family, life phases, ageing, maternity and substance use. The data for this study was collected through focus group discussion, with students reflecting on one question: ‘Do we need cross-border education?’ Data from instructors was collected through discussions during the planning and post-course discussions.Overall, the experiences of students and instructors were positive. The collaboration did not face insuperable challenges. The findings highlighted four main themes: globalization, networking, comparing theory and practice, and using technology. Globalization has set new demands for social work and its professionals. Experts in cultural diversity and international social issues, as well as people with a comparative approach to different societies, are needed the world over. Regarding implications for cross-border education, we would recommend collaboration in the particular field of social work, developing specific courses together supported by both universities and international networks of universities.